Liquidity, Profitability, Firm Size and Leverage on Company Value - Febriana, Hadijah; Anismadiyah, Vega (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
This research aims to determine the effect of liquidity, profitability, firm size and leverage on company value in automotive and component sub-sector manufacturing companies on the Indonesia Stock Exchange with an observation period of 2012 - 2022. The method in this research uses panel data regression analysis and is tested using a program Eviews data processing 12. The population in this study were 13 companies in the automotive and components sub-sector listed on the Indonesia Stock Exchange and 3 companies were used as samples in this study. The partial research results show that: 1) the liquidity variable has no effect on firm value, 2) the profitability variable has a significant effect on firm value, 3) the firm size variable has no effect on firm value, 4) the leverage variable has no effect on firm value and the test results are simultaneously identified that liquidity, profitability, firm size and leverage have a significant effect on company value.